MELATIH KETERAMPILAN GERAK DASAR ANAK MADRASAH MELALUI AKTIVITAS OLAHRAGA - Widodo, Bintoro (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Basic motor ability is the ordinary potency students do to improve the quality of life. Basic motor ability is divided to three categories namely: locomotor, nonlocomotor, and manipulative. Motor ability at all age levels will increase if it’s done through a learning process as learning Physical Education in schools. Motor skills can be coached to improve ability of madrasah children among others: basic motor run, walk, throw, jump, gymnastics, and sports games. Basic motor skills can help developing students toward perfection level of motor in accordance with their age level. Coaching of basic motor skill level is expected students to gain a good development level of motor.Key word: Basic Motor, Sports